Humor Analysis of Monty Python and the Holy Grail - Fauzan Romdhoni Kusnandi; Isti Siti Saleha Gandana; Nia Nafisah (Universitas Pendidikan Indonesia (UPI), 2020)
This study entitled Humor analysis of Monty Python and the Holy Grail (1975) aims to analyzes humor that exists in a British comedy film Monty Python and the Holy Grail (1975), which is directed by Terry Gilliam and Terry Jones, to understand the humor and what the humor implied. Employing textual analysis, this study uses Vandaele's (2002) humor mechanism and film form proposed by Bordwell, Thompson, and Smith (2017) as the tools of analysis. The study indicates that the humor is constructed based on the four contexts as described by Vandaele (2002): (1) (De-) normalization, (2) solution, (3) conditioning, and (4) evaluation. Furthermore, the humor signifies the film author’s credibility to deliver humor that is enjoyable to many people, especially those who have been exposed to western culture. Keywords: film, humor, humor mechanism, incongruity, Monty Python and The Holy Grail.